Lung-Protective Mechanical Ventilation Strategies in Pediatric Acute Respiratory Distress Syndrome. Issue 8 (August 2020) - Wong, Judith Ju Ming; Lee, Siew Wah; Tan, Herng Lee; Ma, Yi-Jyun; Sultana, Rehana; Mok, Yee Hui; Lee, Jan Hau
Abstract : Objectives: Reduced morbidity and mortality associated with lung-protective mechanical ventilation is not proven in pediatric acute respiratory distress syndrome. This study aims to determine if a lung-protective mechanical ventilation protocol in pediatric acute respiratory distress syndrome is associated with improved clinical outcomes. Design: This pilot study over April 2016 to September 2019 adopts a before-and-after comparison design of a lung-protective mechanical ventilation protocol. All admissions to the PICU were screened daily for fulfillment of the Pediatric Acute Lung Injury Consensus Conference criteria and included. Setting: Multidisciplinary PICU. Patients: Patients with pediatric acute respiratory distress syndrome. Interventions: Lung-protective mechanical ventilation protocol with elements on peak pressures, tidal volumes, end-expiratory pressure to FIO2 combinations, permissive hypercapnia, and permissive hypoxemia. Measurements and Main Results: Ventilator and blood gas data were collected for the first 7 days of pediatric acute respiratory distress syndrome and compared between the protocol ( n = 63) and nonprotocol groups ( n = 69). After implementation of the protocol, median tidal volume (6.4 mL/kg [5.4–7.8 mL/kg] vs 6.0 mL/kg [4.8–7.3 mL/kg]; p = 0.005), PaO2 (78.1 mm Hg [67.0–94.6 mm Hg] vs 74.5 mm Hg [59.2–91.1 mm Hg]; p = 0.001), and oxygen saturation (97% [95–99%] vs 96% [94–98%]; p = 0.007) were lower, and end-expiratory pressure (8 cm H2 O [7–9 cm H2 O] vs 8 cm H2 O [8–10 cm H2 O]; p = 0.002] and PaCO2 (44.9 mm Hg [38.8–53.1 mm Hg] vs 46.4 mm Hg [39.4–56.7 mm Hg]; p = 0.033) were higher, in keeping with lung protective measures. There was no difference in mortality (10/63 [15.9%] vs 18/69 [26.1%]; p = 0.152), ventilator-free days (16.0 [2.0–23.0] vs 19.0 [0.0–23.0]; p = 0.697), and PICU-free days (13.0 [0.0–21.0] vs 16.0 [0.0–22.0]; p = 0.233) between the protocol and nonprotocol groups. After adjusting for severity of illness, organ dysfunction and oxygenation index, the lung-protective mechanical ventilation protocol was associated with decreased mortality (adjusted hazard ratio, 0.37; 95% CI, 0.16–0.88). Conclusions: In pediatric acute respiratory distress syndrome, a lung-protective mechanical ventilation protocol improved adherence to lung-protective mechanical ventilation strategies and potentially mortality. Abstract : Supplemental Digital Content is available in the text.